2022
DOI: 10.1039/d2sc00689h
|View full text |Cite
|
Sign up to set email alerts
|

An unprecedented azobenzene-based organic single-component ferroelectric

Abstract: Organic single-component ferroelectrics, as an important kind of metal-free ferroelectrics, are highly desirable for their easy processing, mechanical flexibility, and biocompatibility. However, although nearly 50 years have passed since the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The organic–inorganic hybrid materials (OIHMs) are a hot scientific topic due to their adjustable structure, easy synthesis, and functional features. Compared with traditional pure organic or inorganic materials, OHIMs possess more advanced properties. As one unique property of OHIMs, structural phase transition receives tremendous attention, which can introduce attractive properties, such as switchable dielectric and nonlinear optical switching. Thus, the OHIMs have great application prospects such as data communications, optoelectronic equipment, memories, actuators, sensors, and capacitors. …”
Section: Introductionmentioning
confidence: 99%
“…The organic–inorganic hybrid materials (OIHMs) are a hot scientific topic due to their adjustable structure, easy synthesis, and functional features. Compared with traditional pure organic or inorganic materials, OHIMs possess more advanced properties. As one unique property of OHIMs, structural phase transition receives tremendous attention, which can introduce attractive properties, such as switchable dielectric and nonlinear optical switching. Thus, the OHIMs have great application prospects such as data communications, optoelectronic equipment, memories, actuators, sensors, and capacitors. …”
Section: Introductionmentioning
confidence: 99%
“…Here, the phase below T p is designated as room-temperature phase (RTP) and the phase above T p is assigned as high-temperature phase (HTP). Such a high phase transition temperature is higher than most reported single-component phase transition materials. Additionally, thermogravimetric analysis measurements of 1-R and 1-S showed that decomposition occurred around 550 K (Figure S2), indicating their excellent thermal stability.…”
Section: Resultsmentioning
confidence: 86%
“…The blue dots and the dark blue line are the experimental data and the fitting curve, respectively. (b) Diagram of comparison between different organic ferroelectrics. ,, Note: MDABCO = N -methyl- N ′-diazabicyclo­[2.2.2]­octonium, 1 = di­(benzylamino)-substituted derivative of muconic acid, APFA = 2-amino-2′,4,4′,6,6′-penta-fuoroazobenzene. (c) Correspondence diagram of the SHG intensity and particle size of [HDABCO]­[ l -MA] at room temperature.…”
Section: Resultsmentioning
confidence: 99%